2013
DOI: 10.1080/13218719.2012.729019
|View full text |Cite
|
Sign up to set email alerts
|

Don't be Happy, Worry: Positive Mood, but not Anxiety, Increases Stereotyping in a Mock-Juror Decision-Making Task

Abstract: Moods and emotions have the potential to influence the decisions made by jurors.Two theories predict that when people are anxious they will rely more on stereotypes when evaluating other people. However, research results have been equivocal as to whether anxiety increases the use of stereotypes in evaluations of other people. Study 1 (N = 127) and Study 2 (N = 279) used a juror decision-making task to examine whether anxiety would increase the application of stereotypes, and it did not. However, the same task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Nor did we find evidence that potential anxiety‐related stereotyping improved person memory for out‐group members, which may decrease the OEB. Instead our results are consistent with recent studies which have suggested that anxiety does not increase the use of stereotypes in social judgments (e.g., Curtis, ; Curtis & Locke, , ). However, given the apparent readiness with which people tend to categorize out‐group members and activate relevant stereotypes (Macrae et al, ; Mason, Cloutier & Macrae, ), it seems likely that ethnic categories and associated stereotypes are already highly activated during typical OEB tasks.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nor did we find evidence that potential anxiety‐related stereotyping improved person memory for out‐group members, which may decrease the OEB. Instead our results are consistent with recent studies which have suggested that anxiety does not increase the use of stereotypes in social judgments (e.g., Curtis, ; Curtis & Locke, , ). However, given the apparent readiness with which people tend to categorize out‐group members and activate relevant stereotypes (Macrae et al, ; Mason, Cloutier & Macrae, ), it seems likely that ethnic categories and associated stereotypes are already highly activated during typical OEB tasks.…”
Section: Discussionsupporting
confidence: 93%
“…They were told that the speech would occur at the end of the experiment (i.e., after the face‐recognition task) and that the speech would be recorded on video and would be evaluated by their peers. This anxiety manipulation has been used successfully to increase participants' anxiety in previous studies (e.g., Curtis, ). Control participants were told that they would be viewing and anonymously evaluating other participants' speeches, but that they would not be giving a speech themselves.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the reasoning behind Supreme Court's ultimate decision to uphold the constitutionality of the ACA is likely to be multifaceted, Malphurs and Drescher's (2012) findings shed light on how a positive courtroom atmosphere, induced by humor and laughter, can influence the rulings. In regard to stereotyping, a defense attorney may use humor when presenting his arguments to induce a positive mood among the jury who, in turn, may show leniency towards a defendant who does not fit the gender-crime stereotype (Curtis, 2013).…”
Section: Practical Applicationsmentioning
confidence: 99%